2022
DOI: 10.5114/biolsport.2021.102806
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific response to whole-body vibration training: a randomized controlled trial

Abstract: A few studies have indicated that males and females respond differently to whole-body vibration (WBV) training. However, the existing insights are still insufficient and they cannot be transferred to sex-specific practice planning. To evaluate the effect of 5-week WBV training on neuromuscular [countermovement jump (CMJ), squat jump (SJ)] and cardiovascular [heart rate and blood pressure] data, taking into account sex-specific effects. This is a comparative experimental study including 96 healthy adults, divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Other studies suggested that greatest effect is obtained by using combination of a high amplitude and the frequency (<4mm and 50Hz) (Adams et al, 2009). It still remains inconclusive how to optimise and apply WBV parameters concerning athletes age, experience, gender, type of exercise, body position and health status to maximise the muscle activation and strength gains (Hartard et al, 2022). The present study found that both CMJ (4.7%) and SJ (1.6%) were significantly higher in WBV than RTG following the intervention.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…Other studies suggested that greatest effect is obtained by using combination of a high amplitude and the frequency (<4mm and 50Hz) (Adams et al, 2009). It still remains inconclusive how to optimise and apply WBV parameters concerning athletes age, experience, gender, type of exercise, body position and health status to maximise the muscle activation and strength gains (Hartard et al, 2022). The present study found that both CMJ (4.7%) and SJ (1.6%) were significantly higher in WBV than RTG following the intervention.…”
Section: Discussionmentioning
confidence: 49%
“…Numerous studies showed that WBV can cause a significant positive short- (Dallas, Kirialanis, & Mellos, 2014) and long-term (Hartard et al, 2022) effects on strength, power and sprinting abilities. Previously published meta-analyses showed greater long-term WBV training effects on muscle strength and power than without WBV (Osawa et al, 2013) with vertical platforms eliciting larger effects as compared to oscillating platforms (Marín & Rhea, 2010).…”
Section: Introductionmentioning
confidence: 99%